Water quality dynamics in an experimental serial-use raceway and its effects on growth of South African abalone, Haliotis midae - Naylor, Matthew Aubrey (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
An understanding of species specific water quality requirements is essential for efficient production of aquaculture products, an aspect not well documented for the land-based culture of the South African abalone, Haliotis midae. In order for the industry to remain competitive in international markets, efficient use of water supplies and the development of water reuse technology is needed. This study assessed the changes in water quality between tanks in a tiered serial-use raceway in relation to accumulated biomass and water flow and estimated the flow index (FI) (L hâ »Â¹ kgâ »Â¹) at which growth becomes significantly affected. The effect of dietary protein level, supplementation of pure oxygen and addition of sodium hydroxide (NaOHâ ») on water quality and fundamental production parameters in the serial-use raceways was also assessed. The serial-use raceways were used as a tool to create a range of water quality conditions at which the growth, feed conversion ratio (FCR) and condition factor (CF) of "cocktail" size (60 "“ 70 mm) H. midae could be monitored. The metabolic activity of the abalone resulted in a deterioration in water quality between tanks in series. pH (rÂ² = 0.99; p < 0.001) and dissolved oxygen concentration (rÂ² = 0.99; p < 0.001) were positively correlated with flow index (pH = 7.38 FIÂ°Â·Â°Â² ; dissolved oxygen = 6.92 FIÂ°Â·Â°â ´), while free ammonia nitrogen (FAN) (rÂ² = 0.99, p < 0.001) and nitrite (NOÂ²â » - N) (rÂ² = 0.93, p < 0.001) were negatively correlated with flow index (FAN = 8.02 FIâ »Â°Â·â ·Â¹). Nitrite concentrations increased over time indicating colonisation of Nitrosomonas bacteria on the basket surfaces. A flow index of 7.2 "“ 9.0 L hâ »Â¹ kgâ »Â¹ was estimated as the minimum to avoid significant reductions in weight and shell length gain and increases in FCR values. Total ammonia nitrogen (TAN) and FAN concentrations were significantly correlated to dietary protein (P) (t = 6.63, p < 0.0001 and t = 6.41, p < 0.0001, respectively) and flow index (t = 5.42, p < 0.0001 and t = 3.9, p < 0.0002, respectively) and could be estimated using the models TAN = 9.73 P "“ 110.3 log (FI), and FAN = 0.132 P "“ 1.10 log (FI). Mean FAN concentrations were 67 and 41 % lower in tanks fed a diet containing 22 and 26 % protein respectively, when compared to tanks fed a 33 % protein diet. Supplementation with pure oxygen (103 Â± 8 % saturation) improved shell length gain (t = 3.45, p = 0.026) in abalone exposed to high FAN (2.43 Â± 1.1 Î¼g Lâ »Â¹) and low pH (7.6 Â± 0.13), relative to a treatment with no oxygen supplementation (92 Â± 6 % saturation). Addition of a sodium hydroxide solution resulted in elevated mean pH in treatment raceways when compared to control raceways. The increased pH resulted in significantly higher weight gain (g abaloneâ »Â¹) (Fâ‚ Â·â‚ â‚‚ = 4.51; p = 0.055) and shell length gain (mm abaloneâ »Â¹) (Fâ‚ Â·â‚ â‚‚ = 4.56; p = 0.054) at an Î±-error level of < 5.5 %. In two trials, weight gain and shell length gain were significantly correlated to pH (p < 0.001), and multiple regression of pH, dissolved oxygen and FAN consistently revealed pH to be the best predictor of growth. It is therefore suggested that decreasing pH is the first limiting water quality variable for abalone in serial-use raceways. As a decrease in water pH is linked to respiration by the abalone and subsequent increase in dissolved carbon dioxide (COâ‚‚) concentration, future studies should examine the effects of COâ‚‚ on H. midae metabolic rate, calcification rate and health. The results of this study will contribute toward our understanding of the specific water quality requirements for H. midae in commercial aquaculture systems, and influence the design and management procedures for abalone water reuse systems.
Keywords: Haliotis midae -- South Africa; Abalone culture -- South Africa; Abalones -- Effect of water quality on; Abalones -- Nutrition -- South Africa; Abalones -- Feeding and feeds; Abalones -- Growth; Fish culture -- Water reuse